The efforts of ancient and modern linguists in facilitating Arabic grammar - Gamal El Din, Wagdy Mohamed Ahmed; Al-Amrousy, Mohammed Ahmed; Shafter, Ehab Saad (Arab Journal for Sciences and Research Publishing, 2016)
complains have been became a lot from "syntax" and its difficulty. hence this feeling has become general as for Arabs who became disabled of using a formal language in all sides of life. although "syntax" is considered the scales of Arabic and its strong fort against changes of time. This study aims at clarifying the exhausted efforts which the ancient linguists have done to facilitate "syntax". And attempting to know the basic axles which may take part in facilitating the Arabic syntax through balancing between two team's efforts. these attempts showed that it didn't far away of the public concepts of syntax excepting "Ebn Modaa”, s invitation in his book "answering the grammarians”, but it didn't find any acceptance or spreading it was also about to be forgotten without Dr. Shawky Daif who was eager to introduce a critical sight towards some axles which grammarians depended on. he also refused the destructive invitations and assured the Arabic syntax should not be neglected. the researcher depends on the date of the analytical method, discussing, analyzing and deducing also The study has reached to some results: -  Facility must not be away from society. We should enrich the teacher and also be interested in the learner desires and increasing his motivations towards learning his language. The necessity of returning to the first resources and trying to refresh it with appropriate teaching method and the ages nature.  We also must realize that sciences could not free of difficulty and also to know that language did not handle itself to a stupid learner, so it needs exhausted efforts and a big awareness as syntaxes are not hard to be understood as it is not a strange thing among sciences, but we also facilitate it if only our intentions are purified and efforts are union also.
Keywords: Facilitating Arabic grammar; factor theory; classical and colloquial; Quranic grammar